ANALISIS PERBANDINGAN FAKTOR-FAKTOR PEMBENTUK PERTUMBUHAN EKONOMI NASIONAL DAN KALIMANTAN BARAT DARI SISI PERMINTAAN - B01108077, Rena Erwina (Jurnal Pembangunan dan Pemerataan, 2013)
This study aimed to determine the correlation between economic growth in Indonesia and West Kalimantan and knows comparisons factors forming national economic growth and the demand side of West Kalimantan. The tools used in this research is the analysis of panel data regression models (cross section and time series), with observation data as much 42 on Indonesia and West Kalimantan during the period 1990 to 2010. The processing of the data using computer program SPSS 16. Based on calculations, the results of the regression and the various tests that have been done show that there is a correlation between the growth of Indonesia's economic relations with the economic growth of West Kalimantan. Forming factors of economic growth on the demand side, both nationally and in West Kalimantan is dominated by household expenditure, while the role of the export import small compared to other sectors. Keywords: Economic Growth.